Investigation Of Methods To Reduce The Micro Hardness Of Marble Aggregates (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper describes the surface degradation properties of brittle and plastic-brittle materials like marble, crumbling body properties, load acceleration parameters and effects associated with the environment in which grinding is performed. When applied to marble filler in mosaic coatings, first of all, abrasive erosion occurs and a large number of cemented abrasive grain surfaces are removed by means of grinding binders, i.e. a micro-scratch process.